2004
DOI: 10.1177/153537020422900104
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Proanthocyanidins Derived from Cacao Inhibits Diabetes-Induced Cataract Formation in Rats

Abstract: Proanthocyanidins derived from cacao (CLP) have various antipathophysiological functions. We have tested whether dietary supplementation with CLP prevents cataract formation in rats with diabetes induced by streptozotocin (STZ), using histological, histochemical, and biochemical analyses. Starting at 7 days after the streptozotocin challenge, the animals were fed either a normal diet or a diet containing 0.5% w/w CLP over 10 weeks. There were no significant differences in plasma and urine glucose concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…26,27 In a recent study, proanthocyanidins derived from cacao (CLP) were tested for their preventive effect on cataract development in rats with diabetes induced by streptozotocin. 28 The authors found that dietary supplementation with CLP did not affect hyperglycemia but made a significant change in production of hydroxynonenal, a marker of oxidative stress. Hydroxynonenal was only detected when rats were fed a normal diet without CLP.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…26,27 In a recent study, proanthocyanidins derived from cacao (CLP) were tested for their preventive effect on cataract development in rats with diabetes induced by streptozotocin. 28 The authors found that dietary supplementation with CLP did not affect hyperglycemia but made a significant change in production of hydroxynonenal, a marker of oxidative stress. Hydroxynonenal was only detected when rats were fed a normal diet without CLP.…”
Section: Discussionmentioning
confidence: 98%
“…These observations suggested that the CLP may prevent cataract formation by decreasing oxidative stress induced by hyperglycemia. 28 An IH636 grape seed proanthocyanidin extract effectively suppressed cataract formation in rats. The protective effect was supported by lower GSH and higher MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of these PC oligomers on diabetic cataracts, blood sugar, and blood lipid peroxides have been demonstrated in mice [129,130]. PCs derived from cocoa have also been shown to inhibit diabetes-induced eye lens cataract formation possibly via antioxidant effects [130]. A recent study has shown that type-A PC trimers isolated from the aqueous extract of cinnamon have insulin-enhancing activity in in vitro assays measuring insulin-dependent glucose metabolism [131].…”
Section: Biological Effects Of Pcsmentioning
confidence: 97%
“…The effects of these PC oligomers on diabetic cataracts, blood sugar, and blood lipid peroxides have been demonstrated in mice [129,130]. PCs derived from cocoa have also been shown to inhibit diabetes-induced eye lens cataract formation possibly via antioxidant effects [130].…”
Section: Biological Effects Of Pcsmentioning
confidence: 97%
“…Procyanidins derived from cacao have been found to inhibit diabetes-induced cataract formation in rats [214]. These inhibitory effects are probably due to the antioxidant capacity of proanthocyanidins…”
Section: Diabetes Mellitusmentioning
confidence: 99%